Spectacularization in the print media: analysis of specialized radio magazines - Adami, Antonio; Moreira Dias, Lúcia (Ámbitos. Revista Internacional de Comunicación, 2022)
The article aims to analyze the spectacularization in radio magazines in Brazil in the 1920s, 1930s, 1940s and 1950s. With this theoretical basis, the qualitative method was used for data collection, due to its characteristics that fit the theme of work of historical rescue of communication, particularly of the printed medium. We opted for qualitative research because it has unique steps in data analysis and makes use of different research strategies. Qualitative procedures show different perspectives and we think about the media effects in this context. The research was carried out at the Museu da Imagem e do Som, Arquivo Público and Biblioteca Mário de Andrade in São Paulo and also at the National Library of Rio de Janeiro, among other centers. The research problem lies in the effects that this type of production causes on society and as a result we conclude that the magazines were improving in editorial quality but, with a central focus on showbiz and the market, it led to the trivialization of culture, the generalization of frivolity and the scandalous journalism, which unfortunately persists in the media to this day. The research contributed to the understanding that radio and magazines, where one is a vector of growth of the other, were being built for the spectacularization in society and this at various times has shown to have very dark effects, as it transformed, for example, the political discussion into entertainment and journalism in irresponsibility.